2023
DOI: 10.3390/bioengineering10111316
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Corpus (and Language)-Independent Screening of Parkinson’s Disease from Voice and Speech through Domain Adaptation

Emiro J. Ibarra,
Julián D. Arias-Londoño,
Matías Zañartu
et al.

Abstract: End-to-end deep learning models have shown promising results for the automatic screening of Parkinson’s disease by voice and speech. However, these models often suffer degradation in their performance when applied to scenarios involving multiple corpora. In addition, they also show corpus-dependent clusterings. These facts indicate a lack of generalisation or the presence of certain shortcuts in the decision, and also suggest the need for developing new corpus-independent models. In this respect, this work exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…These results are promising; however, recent studies [ 53 , 54 ] indicated that the models employed for pathological voice detection are typically trained using small-scale data, hindering their ability to perform consistently across diverse datasets. As a result, the performance of these models fluctuates considerably depending on the dataset encountered.…”
Section: Resultsmentioning
confidence: 99%
“…These results are promising; however, recent studies [ 53 , 54 ] indicated that the models employed for pathological voice detection are typically trained using small-scale data, hindering their ability to perform consistently across diverse datasets. As a result, the performance of these models fluctuates considerably depending on the dataset encountered.…”
Section: Resultsmentioning
confidence: 99%